2021
DOI: 10.3390/recycling6040080
|View full text |Cite
|
Sign up to set email alerts
|

Avoidable Household Food Waste: Diagnosing the Links between Causes and Composition

Abstract: Problems associated with the wastage of food intended for human consumption are well known and the discarding of edible but unconsumed food—avoidable food waste—is clearly undesirable. Interventions to reduce avoidable food waste need to be suitably informed: understanding the causes and consequences of avoidable food waste is instructive in this regard. One hitherto unexplored approach to understand better the causes of food waste is to elucidate associations between the composition of avoidable food waste an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…As shown in Figure 6, the main reasons for the waste with households were food spoiling before it can be consumed (32%), not using the entire food ingredients (12%), using only parts and disposing of the rest (12%), or buying excess food (9%). This result corroborates the findings in previous studies (Bravi et al., 2020; Quested et al., 2011; Shaw, 2021). In addition, the results of the different measures of the intention to reduce food waste (upon reflecting on several food waste messages) show that 81% intend to reduce food waste overall, 80% intend to reuse any leftover food in the future, and 51% intend to recycle any leftover food at home.…”
Section: Resultssupporting
confidence: 93%
“…As shown in Figure 6, the main reasons for the waste with households were food spoiling before it can be consumed (32%), not using the entire food ingredients (12%), using only parts and disposing of the rest (12%), or buying excess food (9%). This result corroborates the findings in previous studies (Bravi et al., 2020; Quested et al., 2011; Shaw, 2021). In addition, the results of the different measures of the intention to reduce food waste (upon reflecting on several food waste messages) show that 81% intend to reduce food waste overall, 80% intend to reuse any leftover food in the future, and 51% intend to recycle any leftover food at home.…”
Section: Resultssupporting
confidence: 93%
“…2,22 Additionally, with respect to avoidable household food waste by consumers, it is suggested that the knowledge of the composition of food waste will help classify food waste and the development of target interventions. 23 The food waste issue is gaining increasing attention in the scientic literature. The total number of documents related to food waste scientic research were: 14 984 for the keyword "food waste", 1143 for the combination of "food waste" and "environmental impact", and 616 for the combination of "food waste" and "food security".…”
Section: Introductionmentioning
confidence: 99%
“…2,22 Additionally, with respect to avoidable household food waste by consumers, it is suggested that the knowledge of the composition of food waste will help classify food waste and the development of target interventions. 23…”
Section: Introductionmentioning
confidence: 99%